2019
DOI: 10.3928/1081597x-20190118-01
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Follow-up of Correction of Myopia: Posterior Chamber Phakic Intraocular Lens With a Central Port Design

Abstract: PURPOSE: To assess the long-term correction of moderate to high myopia using a posterior chamber phakic intraocular lens with a central port design. METHODS: Uncorrected (UDVA) and corrected (CDVA) distance visual acuities, refraction, intraocular pressure (IOP), endothelial cell density (ECD), vault, and adverse events over a 5-year period were evaluated retrospectively. RESULTS: A total of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
85
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(101 citation statements)
references
References 24 publications
12
85
2
2
Order By: Relevance
“…However, all these studies evaluated patients implanted with older ICL models. With the present V4c ICL, recent long-term studies [13,14] and meta-analysis reported no postoperative complications [1,2]. Kamiya et al [3] and Takahashi et al [4], in an older patient sample (with 6 months of follow-up) similar to ours, did not report either asymptomatic or symptomatic cataract formation.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…However, all these studies evaluated patients implanted with older ICL models. With the present V4c ICL, recent long-term studies [13,14] and meta-analysis reported no postoperative complications [1,2]. Kamiya et al [3] and Takahashi et al [4], in an older patient sample (with 6 months of follow-up) similar to ours, did not report either asymptomatic or symptomatic cataract formation.…”
Section: Discussionsupporting
confidence: 75%
“…However, our follow-up of 1 year is short and these patients should be kept under follow-up for longer periods. Shimizu et al [13] and Alfonso et al [14] with 5 years of follow-up in younger patients implanted with this lens followed this approach of extended follow-up period (mean ages of 31.9 and 31.2 years, respectively). Our mean ECD at 1 year showed no statistically significant differences with their corresponding preoperative values (2516 ± 234 vs. 2568 ± 332 cells/mm 2 , p � 0.29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Implantable Collamer Lens (ICL; STAAR Surgical Co, Monrovia, California) is a safe and effective option for the correction of myopia [1][2][3][4]. With no corneal excision and few high-order aberrations, it is often the rst choice for surgical correction of high myopia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous methods for determining vaulting involved white-to-white measurement (manually or with imaging systems) or sulcus-to-sulcus measurement using high-frequency ultrasound have been the main methods for vaulting prediction [17,18]. Later, optical coherence tomography (OCT) was added to re ne the prediction [19][20][21]. Recent OCT systems that are built within the operating microscope now allow for more precise eye surgeries [22][23][24].…”
Section: Introductionmentioning
confidence: 99%